Liftoff correction based on the spatial spectral behavior of eddy-current images - Ribeiro, A. L.; Alegria, F.; Postolache, O. A.; Geirinhas Ramos, H. M. (IEEE Transactions on Instrumentation and Measurement, 2010)
In this paper, a new processing scheme for compensating the liftoff effect is proposed to increase the signal-to-noise ratio of measurements carried out when a duralumin plate with artificially manufactured defects was scanned with eddy-current probes. The mathematical algorithm is based on the spatial frequency behavior of the output signals with the liftoff distance (the distance between the probe used for inspection and the sample) and its equivalent form (deconvolution) in the spatial domain. Results are presented for measurements performed at three different distances for the same defect of the duralumin plate.